POSSIBILITIES OF USING MEAT PRODUCTS OF INDUSTRIALLY MANUFACTURED BEIKOST FOR ALLERGY PREVENTION IN CHILDREN OF 0–1 YEARS OF AGE - T. V. Turti; T. E. Borovik; L. S. Namazova-Baranova; E. P. Zimina; O. L. Lukoyanova; I. V. Davydova; M. A. Snovskaya (Педиатрическая фармакология)
Critical periods of atopic status formation in children of 0-1 years of age dictate the need in search and introduction to practice of effective allergy prevention methods. The aim of this study is to substantiate efficacy of using hypoallergenic beikost products on the basis of turkey or rabbit meat for prevention of atopic disease and polyvalent allergy development. The study participants are children over 6 months of age with compromised family allergology anamnesis and mild skin manifestation of allergy. The results have confirmed low sensitizing potential of the studied beikost products, good tolerability and efficacy of use for the prevention of atopic process development. The obtained results allow recommending the studied turkey or rabbit meat purees to the risk group children and children with allergy as primary/secondary allergy preventive means and within therapeutic diets.